Postcontact Cultural Perseverance on the Central California Coast: Sedentism and Maritime Intensification. Issue 3 (July 2022) - Jones, Terry L.; Hildebrandt, William R.; Wohlgemuth, Eric; Codding, Brian F.
Abstract : Indigenous people throughout North America were dramatically affected by the invasion of European colonizers. Growing evidence suggests that, among many strategies for survival and perseverance, increased sedentism was common; it often resulted from either forced resettlement or attempts to access European resources. We present artifactual, paleoethnobotanical, and faunal findings from the yak tichu tichu yak tilhini northern Chumash village of Tstyiwi (CA-SLO-51/H) where a reasonably discrete postcontact component provides evidence for extreme resource intensification and year-round site use following contact. Although there is evidence for diachronic settlement shifts preceding arrival of the Spanish, the postcontact occupation at Tstyiwi contrasts significantly with 35 exclusively pre-invasion components in its seasonal profile, artifact diversity, density of plant remains, and abundance of fishing equipment and fish bone. High frequencies of the latter two features seem to reflect use of a resource that became the primary focus of subsistence for this coastal community as its inhabitants intensified their work effort to levels never before seen in attempts to avoid the Spanish whose presence had restricted their foraging radius.